Effect of different positioning before, during and after surgery on pressure injury: a randomized controlled trial protocol - Guler, Bedia; Gurkan, Aysel (International Journal of Clinical Trials, 2024)
Background: Patients undergoing surgery are at risk of developing pressure injuries because they remain immobile and in a fixed position on the operating table for a long time under anesthesia. Prevention of surgery-induced pressure injuries is the best strategy and requires risk assessment and timely implementation of preventive interventions. This trial aims to evaluate the effect of positioning in a different position pre-operatively and post-operatively than the position adopted during surgery on pressure injuries. Methods: This trial was designed as a prospective randomized controlled study. Participants meeting the inclusion criteria will be assigned to the intervention or control groups using a random number generator. The participants in the intervention group will be placed in different positions than their surgical position during the night before surgery, and the first 36 h after surgery. The control group will receive only routine care. The groups will be evaluated in terms of pressure injury development for at least 72 h, until discharge. Conclusions: Surgery-induced pressure injuries have important effects on patients, healthcare professionals, and healthcare organizations. Current guidelines recommend that patients be positioned in a different position preoperatively and postoperatively than the surgical position to redistribute the pressure generated during surgery. There is a need for well-designed, comprehensive studies to investigate the effectiveness of this weak evidence-level recommendation. This trial will provide valuable evidence to inform clinical practice, guide surgical nurses, and allow evaluation of the effects of this intervention. Trial registration: Clinical trials registration number NCT05549830